The Spillover Effects of Russia's Economic Slowdown on Neighboring Countries - Stepanyan, Ara (Spillover Notes; Spillover Notes, 2016)
In the face of sharply lower oil prices and geopolitical tensions and sanctions, economic activity in Russia decelerated in late 2014, resulting in negative spillovers on Commonwealth of Independent States (CIS) and, to a lesser extent, on Baltic countries. The spillovers to eastern Europe have been limited. The degree of impact is commensurate with the level of these countries' trade, remittances, and foreign direct investment (FDI) links with Russia. So far, policy action by the affected countries has focused on mitigating the immediate consequences of spillovers.